2017
DOI: 10.1007/s00726-017-2452-z
|View full text |Cite
|
Sign up to set email alerts
|

Biased selection of propagation-related TUPs from phage display peptide libraries

Abstract: Phage display is rapidly advancing as a screening strategy in drug discovery and drug delivery. Phage-encoded combinatorial peptide libraries can be screened through the affinity selection procedure of biopanning to find pharmaceutically relevant cell-specific ligands. However, the unwanted enrichment of target-unrelated peptides (TUPs) with no true affinity for the target presents an important barrier to the successful screening of phage display libraries. Propagation-related TUPs (Pr-TUPs) are an emerging bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…Consequently, these peptides show a higher than expected frequency within the library [53]. By performing fewer rounds of selection, the bias can be reduced by decreasing the loss of relevant sequences [54].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these peptides show a higher than expected frequency within the library [53]. By performing fewer rounds of selection, the bias can be reduced by decreasing the loss of relevant sequences [54].…”
Section: Discussionmentioning
confidence: 99%
“…The HIAYPRH peptide (Table 4) is an illustrative example of a TUP that somehow remains overlooked by numerous research groups up until now. It was first reported by Lee [28] in 2001 as a TfR ligand but in 2007 Brammer and co-workers [29] demonstrated that it was actually a TUP and later on it was also listed as a TUP in some reviews on this topic [24][25][26]. Furthermore, 30 entries can be found in the BDB for 21 different targets, clearly supporting that it is indeed a TUP.…”
Section: Limitations Of Phage Display and Targeted Deliverymentioning
confidence: 90%
“…Secondly, phage display can be biased, and it is common to come across target unrelated peptides (TUPs) [23][24][25][26]. These motifs do not bind the actual target, but other elements in the system, mostly the polystyrene of which common labware is made, bovine serum albumin, streptavidin, antibodies and bivalent metal ions.…”
Section: Limitations Of Phage Display and Targeted Deliverymentioning
confidence: 99%
“…However, it suffers a lot from all kinds of false positive peptides, which do not bind to or only bind to the target non-specifically. These peptides are so-called targetunrelated peptides (TUP) [37][38][39][40]. With recent advances on bioinformatics studies in this field, there are currently a series of computational resources that can help to deal with this problem [41].…”
Section: Figure 2 Schematic Diagram Of Romiplostimmentioning
confidence: 99%